ChatGPT in English Learning for Non-English Majors: A Systematic Literature Review - Hidayah, Amanda Nurul; Yuliana, Yohanes Gatot Sutapa; Susilawati, Endang; Ikhsanudin, Ikhsanudin (Journal of English Language and Education, 2025)
This systematic literature review investigates the usage of ChatGPT for the learning of English language among non-English majors. Drawing on ten recent research from the last two years, this study looks at students’ perspectives, the impact on language skills, and the challenges of incorporating ChatGPT into learning contexts. The findings show that ChatGPT improves vocabulary acquisition, academic writing, and conversational skills by giving tailored feedback and a low-pressure practice environment. However, issues regarding dependence, ethical use, and the need for teacher direction persist. This paper emphasizes the likelihood of ChatGPT as a complementary learning tool, emphasizing the significance of mixing AI technology with traditional instruction and cultivating AI literacy in order to maximize benefits while maintaining academic integrity.